1 2 1 2 + 2 2 ( 1 + 2 ) 2 + ⋯ + 1 6 2 ( 1 + 2 + 3 + ⋯ + 1 6 ) 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution. A slight variation starting at line 2 would be
n = 1 ∑ 1 6 ( 2 n + 1 ) 2 = 4 1 ( n = 1 ∑ 1 7 ( n 2 ) − 1 ) =
4 1 ( 6 1 7 ∗ ( 1 7 + 1 ) ∗ ( 2 ∗ 1 7 + 1 ) − 1 ) = 2 4 1 ( 1 0 7 1 0 − 6 ) = 4 4 6 .
To make life easier, we have
n = 1 ∑ 1 6 n 2 [ 2 n ( n + 1 ) ] 2 = n = 1 ∑ 1 6 4 ( n + 1 ) 2 .
It is not hard to evaluate the last summation since it is just equal to
4 2 2 + 3 2 + 4 2 + . . . + 1 6 2 + 1 7 2 = 4 6 1 7 ( 1 8 ) ( 3 5 ) − 1 = 4 4 6 .
(1+2)+2 = 1,5; (1+2+3)÷3 = 2; (1+2+3+4)÷4 = 2,5
AP: 1; 1,5; 2; 2,5; 3; 3,5; ...; (1+2+3...+16)÷16
an = a1 + (n-1) • r
a16 = 1 + (16-1) • 0,5
a16 = 8,5
1² + 1,5² + 2² + 2,5² + ... + 8,5² = 446
Problem Loading...
Note Loading...
Set Loading...
1 2 1 2 + 2 2 ( 1 + 2 ) 2 + ⋯ + 1 6 2 ( 1 + 2 + 3 + ⋯ + 1 6 ) 2 = ? n = 1 ∑ 1 6 ( n ∑ k = 1 n k ) 2 = n = 1 ∑ 1 6 n 2 [ 2 n ( n + 1 ) ] 2 =
n = 1 ∑ 1 6 4 ( n + 1 ) 2 = n = 1 ∑ 1 6 ( 4 n 2 + 2 n + 4 1 ) = 4 + 2 1 n = 1 ∑ 1 6 n + 4 1 n = 1 ∑ 1 6 n 2 = 4 + 6 8 + 3 7 4 = 4 4 6